Effect of competition stress on tests used to assess testosterone administration in athletes - Guezennec, C. Y.; Lafarge, J. P.; Bricout, V. A.; Merino, D.; Serrurier, B. (International Journal of Sports Medicine, 1995)
The drug test for exogenous administration of testosterone is based on the testosterone/epitestosterone ratio (T/E) in urine. Physiological and psychological stresses may alter plasma testosterone concentrations. The question is to know how much the psychological conditions of competition can modify the T/E ratio. In order to study this issue, 20 athletes practising modern pentathlon participated in a study designed to determine the effects of a pistol shooting trial on their hormonal response. Pistol shooting induces a high psychological stress without increasing energy expenditure. Venous blood samples were drawn before and after the trial according to the usual drug testing procedure. Athletes were separated into two groups: a group of young athletes (n = 10; mean age 19 +/- 0.3 years) and another group of aged subjects (n = 10; mean age 45 +/- 1.5 years). The rise in plasma testosterone concentrations reached 75% in older subjects versus 55% in younger ones. The plasma luteinizing hormone (LH) concentrations were not influenced by the trial. After shooting trial the elevation in cortisol concentrations was greater for older subjects than for younger ones (273 +/- 30 ng.ml-1 vs 173 +/- 7 ng.ml-1). The catecholamine response was identical in both groups. The urinary T/E ratio remained unchanged after the shooting trial and always remained lower than the International Olympic Committee limit of 6. These results indicate that the psychological stress associated with competition increases the production of steroid hormones (testosterone, cortisol), and that this phenomenon is more pronounced in older athletes. These hormonal changes do not influence the urinary excretion of steroid metabolites used as criterion for drug testing.